If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(d + 4) = 72 Reorder the terms: 3(4 + d) = 72 (4 * 3 + d * 3) = 72 (12 + 3d) = 72 Solving 12 + 3d = 72 Solving for variable 'd'. Move all terms containing d to the left, all other terms to the right. Add '-12' to each side of the equation. 12 + -12 + 3d = 72 + -12 Combine like terms: 12 + -12 = 0 0 + 3d = 72 + -12 3d = 72 + -12 Combine like terms: 72 + -12 = 60 3d = 60 Divide each side by '3'. d = 20 Simplifying d = 20
| -2-(-3)=23 | | X-2-6x-2x=-9 | | 3+4x-7= | | 18=2b-14 | | -10+(-28)= | | (1.6*10^8)(5.8*10^6)/(4*10^6) | | 8z+36=68 | | 5x^3=3600 | | y=-3(x-2)+5 | | 69+66= | | 7n+15-10n=180 | | 4x+28=70 | | 3(7)-4y=-19 | | -3x-5=100 | | 6n-1+5=-20 | | 3456x+56x=4567.89x-2 | | 2n-3n+5n= | | 47-43=180 | | 9x^2-131x+410=0 | | 18m=15 | | 5(2m+3)=95 | | 215+3x=165 | | 3(-1)-y=3 | | 6x-17+40=180 | | X/4-7/4= | | 165+3x=215 | | 9x^6/12x^2 | | 12(f+10)=156 | | 83/4÷70 | | 5+7r+6-4r= | | 12+4(-6)=12 | | 4b+39=63 |